THE DYNAMICS OF ENTREPRENEURIAL MOTIVATION AMONG WOMEN: A COMPARATIVE STUDY OF BUSINESSWOMEN IN SAUDI ARABIA AND BAHRAIN - Muhammad A. Sadi,; Basheer M. Al-Ghazali, (Asian Academy of Management Journal, 2012)
This study explores the underlying dynamics of motivation for women entrepreneurs in Saudi Arabia and Bahrain, using t-test and ANOVA analyses. Various distinct motivational factors were found in both countries. Self-achievement was the most prominent factor motivating Saudi women to start their own businesses. However, for Bahraini women, the profit motive was the most prominent motivational factor.